Participation in Pension Programs in Low and Middle Income Countries - John T. Giles; Clement Joubert; Tomoaki Tanaka (Institute of Labor Economics (IZA), 2025)
Low- and middle-income countries are aging rapidly but stagnation of growth in participation in pension programs, due to widespread informal employment, presents a major fiscal challenge. Some claim that improving the design of pension program rules can encourage more pension contributions, while others push for universal non-contributory pensions. This paper reviews the recent academic literature on the determinants of active participation in pension systems in high-informality settings. An emerging body of evidence shows that participation responds significantly to financial incentives as well as nonfinancial obstacles. At the same time, pensions are imperfect substitutes for other strategies to cover longevity risk, including support through the family, which will remain crucial for many older people in fiscally constrained environments. Therefore, policy makers should integrate the design of contributory pensions, social pensions, and policies that facilitate other forms of elderly support, and consider how all three interact. To inform such efforts, these interactions must be more systematically investigated and the empirical evidence must be expanded beyond a small number of middle-income countries.
Keywords: H55; G51; 330; informality; savings; retirement; pensions; LMICs